2011
DOI: 10.1002/chem.201103037
|View full text |Cite
|
Sign up to set email alerts
|

New Sandwich‐Type Phthalocyaninato–Metal Quintuple‐Decker Complexes

Abstract: Linked and fused arrays, as well as stacked multidecker complexes, with basic tetrapyrrole units as important p-conjugated systems, are of significant interests for advanced molecular materials with potential applications in the field of organic field transistors (OFETs), [1] nonlinear optics (NLO), [2] and solar cells. [3] Efforts towards extended tetrapyrrole motifs have led to new synthetic methodologies that have resulted in new tetrapyrrole systems with one-, [4] two-, [5] and even three-dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 75 publications
1
47
0
Order By: Relevance
“…Both EPR and electrochemical data were suggestive of a reversible dissociation of these triple-decker systems in solution [261,262]. Work done by Cook and coworkers stimulated an additional interest toward the preparation of heteronuclear rareearth/cadmium complexes with four or more tetrapyrrolic ligands [34][35][36][37][38][39][40][41][42].…”
Section: Monophthalocyanine Based Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both EPR and electrochemical data were suggestive of a reversible dissociation of these triple-decker systems in solution [261,262]. Work done by Cook and coworkers stimulated an additional interest toward the preparation of heteronuclear rareearth/cadmium complexes with four or more tetrapyrrolic ligands [34][35][36][37][38][39][40][41][42].…”
Section: Monophthalocyanine Based Techniquesmentioning
confidence: 99%
“…During the next 50 years, it was confirmed that rare-earth ions are capable of the formation of phthalocyanine single-, double, and triple-decker complexes and their analogues [22][23][24][25][26][27][28][29][30][31][32][33]. One of the interesting recent discoveries was the preparation and characterization of heteronuclear (rareearth / cadmium) multiple-decker complexes, which contain up to six Pc ligands [34][35][36][37][38][39][40][41][42].…”
mentioning
confidence: 99%
“…[46] This method was extendedb yW ang et al,a nd their researchg roup has reported the synthesis of multiple-decker complexes with five (quintuple-decker:L n 2 Cd 2 )a nd six (sextuple-decker:L n 2 Cd 3 )l igands, as shown in Figure 1. [47][48][49] These multiple-decker complexes have different intramolecular LnÀLn distances. By changingt he Ln III ion to amagnetically anisotropic ion such as Tb III dipole-dipole (MD) interactions.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34] Researches of both the first sandwich-type rare earth metal double-decker complexes with N-confused porphyrinato and phthalocyaninato ligands [35] and (phthalocyaninato)/(phthalocyaninato)(porphyrinato) rare earth(III)-cadmium(II) quadruple/quintuple/sextuple-decker complexes have been started. [36][37][38][39][40] Spectral and applied properties of the complexes are studied as a rule. Porphyrin and phthalocyanine double-and triple-decker complexes exhibit promising properties such as high stability of neutral and oxidized forms, solubility in organic solvents and ability to self-organization in solid layers.…”
Section: Introductionmentioning
confidence: 99%